Lipid Alterations in Systemic Sclerosis - Gogulska, Zuzanna; Smolenska, Zaneta; Turyn, Jacek; Mika, Adriana; Zdrojewski, Zbigniew (Frontiers in Molecular Biosciences, 2021)
Background: Systemic sclerosis (SSc) is an autoimmune disease with an elusive etiology and poor prognosis. Due to its diverse clinical presentation, a personalized approach is obligatory and needs to be based on a comprehensive biomarker panel. Therefore particular metabolomic studies are necessary. Lipidomics addressed these issues and found disturbances in several crucial metabolic pathways. Aim of Review: The review aims to briefly summarize current knowledge related to lipid alterations in systemic sclerosis, highlight its importance and encourage further research in this field. Key scientific Concepts of Review: In this review, we summarized the studies on the lipidomic pattern, fatty acids, lipoproteins, cholesterol, eicosanoids, prostaglandins, leukotrienes, lysophospholipids, sphingolipids in systemic sclerosis. Researchers demonstrated several alternate aspects of lipid metabolism. As we aimed to present our findings in a comprehensive view, we decided to divide our findings into three major groups “Serum lipoproteins”, “fatty acids and derivatives” and “cellular membrane components” as we do believe, they play a prominent role in role in SSc pathology.